Pengembangan Lembar Kerja Siswa Berbasis Metode Mind Map Pada Mata Pelajaran IPA Di Sekolah Dasar - Muhammad Irfan (Universitas Negeri Makassar, 2017)
This study aims to determine how the description of validity, practicality and effectiveness of Student Worksheet Based Mind Map in Primary School has been developed. This research is designed in descriptive form to explain exactly what is the development of Student Worksheet Based on Mind Map. The use of descriptive method aims to obtain an overview of the development of Mind Map Student Worksheet in depth, detailed and intact with regard to its validity, practicality and effectiveness. The type of data taken is descriptive quantitative data type, where data is taken from direct observation by the researcher related to LKS development, LKS validation and limited trial through science learning using LKS based on Mind Map which have been prepared. The results of the research are: 1) LKS based on Mind Map of development result stated valid, practical and effective and feasible to be used in elementary school science teaching based on expert validation result, legality test by student and teacher response. 2) The result of LKS test based on Mind Map shows satisfactory result that is the average ability of scientific work of student equal to 85% with very good category and result of student learning reach completeness learn classically with achievement equal to 82,7%